Efficacy of suit therapy on functioning in children and adolescents with cerebral palsy: a systematic review and meta‐analysis. (27th November 2015) - Martins, Elisabete; Cordovil, Rita; Oliveira, Raul; Letras, Sara; Lourenço, Soraia; Pereira, Inês; Ferro, Ana; Lopes, Inês; Silva, Claudia R; Marques, Marta
Abstract : Aim: This systematic review and meta‐analysis presents an overview of the efficacy of suit therapy on functioning in children and adolescents with cerebral palsy (CP). Method: A systematic review with meta‐analysis was conducted. A comprehensive search of peer‐reviewed articles was performed on electronic databases, from their inception to May 2014. Studies included were rated for methodological quality using the Physiotherapy Evidence Database scale. Effects of suit therapy on functioning were assessed using meta‐analytic techniques. Results: From the 46 identified studies, four met the inclusion criteria and were included in the meta‐analysis. Small, pooled effect sizes were found for gross motor function at post‐treatment ( g =0.46, 95% confidence interval [CI] 0.10–0.82) and follow‐up ( g =0.47, 95% CI 0.03–0.90). Interpretation: The small number of studies, the variability between them, and the low sample sizes are limitations of this review. Findings suggest that to weigh and balance benefits against harms, clinicians, patients, and families need better evidence to examine and prove the effects of short intensive treatment such as suit therapy on gross motor function in children and adolescents with CP. Therefore, more research based on high‐quality studies focusing on functioning in all dimensions of the International Classification of Functioning, Disability and Health perspective is necessary to clarify the impact of suit therapy. What this paper adds: Suit therapy interventions have limited and heterogeneous effects on gross motor function. Limitations of evidence on suit therapy should be considered when advising parents. Provides a basis for future research studies on the implementation and effectiveness of suit therapy in children and adolescents with CP. This article is commented on by Bailes on pages322–323 of this issue.